Sufism, Islamic Work Ethic, and Professionalism in Improving Welfare - Waluyo Waluyo; Aminullah; Zahwan Anwar (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2026)
This study aims to examine the relevance of Sufism teachings in modern life by exploring the correlation among worship (ibadah), work ethic, and professionalism, and the influence of Sufi practice on various life aspects (religious, social, and career). The quantitative approach was employed using a survey of 150 respondents employed in public and private institutions in Surakarta. Instruments included worship scale, Islamic work ethic scale, professionalism scale, and a Sufi practice scale. Data was analyzed using Pearson correlation and multiple regression. Results showed significant positive correlations between worship & work ethic (r = 0.65, p < 0.01), worship & professionalism (r = 0.58, p < 0.01), and work ethic & professionalism (r = 0.72, p < 0.01). Sufi practice simultaneously had a significant effect on life satisfaction, emotional stability, and work productivity, with R² = 0.55. The novelty of this study is the integration of the Sufi practice variable, which has been rarely included in previous work-ethics-professionalism models in Indonesia’s modern context. The study fills an empirical gap regarding how Sufism moves beyond spiritual dimension into work and professional dimensions